ASME 2009 InterPACK Conference, Volume 2 2009
DOI: 10.1115/interpack2009-89065
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement Using Laminar Gas-Liquid Segmented Fluid Streams

Abstract: Heat transfer enhancement using segmented non-boiling gas-liquid streams is examined. Segmentation results in a two phase flow of liquid/gas having a constant liquid fraction, i.e. no phase change occurs. In this flow configuration, enhanced heat transfer occurs as a result of a shorter effective thermal length and internal fluid circulation in the liquid plugs. A simple theory for laminar segmented flows is developed based on Graetz theory and comparisons made with existing data from the literature and new da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…These were noted by Oliver and Wright [24] and include an increased velocity of the liquid phase due to the addition of a segmenting gaseous phase and an internal circulation within liquid slugs, as was recently measured by King et al [25] using Particle Image Velocimetry in microchannels. Muzychka et al [26] have shown analytically that flow segmentation, resulting in increased fluid velocity alone, cannot account for increased heat transfer rates over single phase or long solid plug flows. Hence the physical mechanism driving enhanced heat transfer must either result from the internal circulation, or a modified velocity profile within liquid slugs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These were noted by Oliver and Wright [24] and include an increased velocity of the liquid phase due to the addition of a segmenting gaseous phase and an internal circulation within liquid slugs, as was recently measured by King et al [25] using Particle Image Velocimetry in microchannels. Muzychka et al [26] have shown analytically that flow segmentation, resulting in increased fluid velocity alone, cannot account for increased heat transfer rates over single phase or long solid plug flows. Hence the physical mechanism driving enhanced heat transfer must either result from the internal circulation, or a modified velocity profile within liquid slugs.…”
Section: Introductionmentioning
confidence: 98%
“…A small number of authors have experimentally [19][20][21][22] and more recently numerically [27][28][29] investigated the influence of slug length on heat and mass transfer characteristics. Table 1 summarizes the experimental variables of these studies and an in-depth analysis of their results was recently published by the authors [26]. The focus of the experimental studies listed in Table 1 was on bulk tube heat transfer with an isothermal wall boundary condition, although the numerical studies do show local heat transfer rates.…”
Section: Introductionmentioning
confidence: 99%
“…The final step is to characterize anticipated pumping pressure penalties through examination of pressure drop measurements [16], or an assumption of Newtonian flow behavior could be made, in which case conventional pressure drop predictions can be employed. Finally, it is also noted that further heat transfer enhancements could be achieved in MPCM slurry flows were a two-phase gas-liquid flow regime similar to that previously employed by the presented authors [32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 82%
“…One is a result of the internal circulation in the liquid plugs, leading to greater radial transport of heat or mass, while the other mechanism results from the increased velocity that liquid plugs experience as a result of the reduced liquid fraction for a constant mass flow rate. The latter was shown to be impossible by Muzychka et al [1] using simple heat transfer theory. While the mean heat transfer coefficient is increased with increase in local velocity, the reduced contact area leads to larger deficits in overall heat transfer rates.…”
mentioning
confidence: 96%
“…While these studies carefully examined the effect of void fraction and plug length on heat transfer enhancement using carefully planned experiments, they failed to consider plug length as an ac-tual scaling parameter in heat transfer predictions. The data from these and other studies was re-analyzed by Muzychka et al [1] using different scaling principles. In Walsh et al [2], the authors considered the constant flux boundary condition and performed careful measurements with electrically heated tubes.…”
mentioning
confidence: 99%